Determining granule size of Cyperus rotundus tuber-based bioherbicide for weed control in upland rice - Rizki Fadilah Rohman; Muhamad Achmad Chozin (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2025)
The application of granular bioherbicides derived from purple nutsedge (Cyperus rotundus L.) tubers offers an environmentally friendly alternative for managing weed competition in upland rice cultivation. This study evaluated the efficacy of various granular bioherbicide forms and sizes (67.5 kg ha-1) in suppressing weed growth and their impact on upland rice. A completely randomized design with twelve treatments was employed. Results showed that granular bioherbicides effectively controlled broadleaf weeds for up to four weeks without causing phytotoxicity to upland rice. Very small granular bioherbicides (spherical and cylindrical) were the most effective form to suppress weed growth of Alternanthera sessilis (L.) R.Br. ex DC., and Mimosa pudica L., and enhance upland rice growth and yield. Keywords: allelopathy; biological control; efficacy; pre-emergence; sustainable agriculture